PENERAPAN TEKNOLOGI TEST KIT KEBUNTINGAN TERNAK SAPI PADA KELOMPOK TERNAK SALINGKA KAMPUS DI KOTA PADANG - Ferry Lismanto Syaiful; Jaswandi Jaswandi; Hendri Hendri; Masrizal Masrizal; Khasrad Khasrad; Rusdimansyah Rusdimansyah (Jurnal Hilirisasi IPTEKS, 2023)
Animal pregnancy testing is one of the techniques/tools used to detect animal pregnancy. This livestock pregnancy test kit can identify early pregnancy in beef cattle, which is useful for farmers to take appropriate actions in reproductive management and cattle care. The objectives of this activity are: 1. to improve farmers' knowledge of early pregnancy detection and the cattle reproduction process to increase the birth rate of calves, 2. to enhance farmers' skills in early pregnancy detection in cattle to improve efficiency in farm operations, and 3. to disseminate early cattle pregnancy technology using pregnancy test kits to farmer groups within the campus community in Padang City. This activity was conducted in a cattle group within the campus community located in Pauh Subdistrict, Padang City. The methods of this activity included counseling, training/demonstration, and evaluation. Participants in this activity were the Taruko Sakato Farmer Group, lecturers, and students from the Faculty of Animal Husbandry, Andalas University. The results of this activity were that participants understood the principles of the test kit, collected necessary urine samples, and improved their skills and understanding in independently and accurately detecting animal pregnancy. The application of this cattle pregnancy test kit technology is expected to assist farmers in enhancing productivity and efficiency in cattle reproductive and production management, thereby positively impacting farmers and local food security. In conclusion, this activity provided knowledge, understanding, and practical skills to farmer groups/partners in adopting innovative technology for improving their livestock farming outcomes.